Mochima theoretical physics spring school - Berche, B.; Donoso, A.; Paredes, R. (Condensed Matter Physics, 2006)
The Mochima theoretical physics spring school on the Foundations of statistical and mesoscopic physics took place in Mochima, Edo. Sucre, Venezuela, between the 20th and 24th of June 2005. The Mochima biological station, 400 km east from Caracas, is devoted to the study of the sea fauna of the Mochima National Park in the Caribbean sea. This scientific event, between conventional school and informal workshop, aimed at providing a current overview of the general field of Statistical Physics and Mesoscopic Physics and at fostering interaction among active physicists coming from different countries and postgraduate students from Venezuela in this area.